Implementation of Physical Education Teachers Learning During The Covid-19 Pandemic in Nias Barat District - Hulu, Aldin; Nasution, Usman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research is a descriptive quantitative research with One Shot Case Study approach and survey method. The objective of this research is to know and to analyze the implementation of Physical Education learning during COVID-19 pandemic in Kabupaten Nias Barat. The sample of this research is 47 certified PJOK teachers from 38 Public Elementary Schools Kabupaten Nias Barat. This research has 9 indicators used as the standard to measure the implementation level of Physical Education learning process during COVID-19 Pandemic. The results of this research are: (1) indicator 1, 94.89%; (2) indicator 2, 74.15%; (3) indicator 3, 90.96%; (4) indicator 4, 64.98%; (5) indicator 5, 90.96%; (6) indicator 6, 79.76%; (7) indicator 7, 89.63%; (8) indicator 8, 73.05%; (9) indicator 9, 79.79%. From the 9 indicators above, it can be concluded that the implementation level of Physical Education learning during Covid-19 pandemic in Public Kabupaten Nias Barat has the percentage of 82,01% which can be categorized as great.